Multifunctional flexible composite material with fine structure as well as preparation method and application of multifunctional flexible composite material
By designing a micro-protruding structure on the surface of the aramid fiber cloth and alternately setting it with the UHMWPE matrix, combined with the gradient distribution arrangement method, the problems of poor interface adhesion and stress concentration of traditional composite materials are solved, and the impact toughness and interface performance of the material are significantly improved.
Patent Information
- Application Number
- CN202411825747.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional polymer composite materials perform poorly in impact and vibration applications, mainly due to poor interfacial adhesion and stress concentration problems, making it difficult to simultaneously improve the impact toughness and other properties of the material.
The aramid fiber cloth with a micro-protruding structure is used to alternately arrange with the ultra-high molecular weight polyethylene (UHMWPE) matrix, and the interface performance and impact toughness are improved through the arrangement of gradient distribution.
It significantly improves the interface bonding force and impact toughness of the material, reduces interface peeling and slippage, enhances the overall performance of the material, and is suitable for aerospace, automobiles, sports equipment and protective equipment and other fields.
Smart Images

Figure CN119636208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer composite materials, and in particular relates to a multifunctional flexible composite material with a fine structure and a preparation method and application thereof. Background Art
[0002] Polymer composites are composite materials composed of polymer materials (usually polymers) and other materials (reinforcement phases such as fillers and fibers). These materials can significantly improve their mechanical properties, thermal properties, chemical stability and other functional properties, and are therefore widely used in aerospace, automobiles, sports equipment, protective equipment and other fields.
[0003] In polymer composite materials, the interface performance between the matrix and the reinforcement phase directly affects the mechanical properties of the material. As the requirements for materials in the use environment continue to increase, especially in applications that are subject to impact and vibration, higher requirements are placed on the impact toughness and stress wave dispersion capabilities of the materials. Traditional structural designs fail to effectively solve the problems of poor interface adhesion and stress concentration, resulting in poor performance of the materials in practical applications. Therefore, it is particularly important to develop composite materials with superior interface performance and improved impact toughness.
[0004] For impact applications, the impact toughness of materials is particularly critical. Traditional polymer composites often improve impact toughness through surface treatment, adding interface modifiers, introducing flexible interface layers and functional coatings, but these methods are easily affected by the external environment, which in turn affects the stiffness, strength and heat resistance of the material. Therefore, it is necessary to study a new structural design strategy that can improve both interface performance and impact toughness, which can improve the impact toughness of the material without affecting other properties.
[0005] Gradient distribution structure can effectively regulate stress distribution, reduce stress concentration and improve the comprehensive performance of materials by realizing functional gradient. The arrangement of reinforcement phase, especially the design of gradient distribution, has not been fully studied yet, especially the specific implementation plan and its effect still need to be further explored to meet more stringent application requirements. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art to at least some extent. The present invention provides a multifunctional flexible composite material with a microstructure, which improves the interface performance of the material and enhances the impact toughness through an innovative micro-protrusion structure design and a gradient distribution arrangement.
[0007] Specifically, the present invention provides the following technical solutions:
[0008] The first aspect of the present invention provides a multifunctional flexible composite material with a microstructure, comprising an ultra-high molecular weight polyethylene matrix and adjacent aramid fiber cloth,
[0009] The ultra-high molecular weight polyethylene matrix is located on the surface of the aramid fiber cloth, and the ultra-high molecular weight polyethylene matrix and the aramid fiber cloth are arranged alternately;
[0010] The surface of the aramid fiber cloth has a micro-convex structure.
[0011] This composite material uses ultra-high molecular weight polyethylene (UHMWPE) as the matrix and aramid fiber cloth as the reinforcement phase. The interface is improved by designing a micro-convex structure (such as rectangular, triangular, and sinusoidal), and the polyethylene matrix and aramid fiber cloth are alternately arranged to significantly improve the interface performance and impact toughness of the material.
[0012] According to an embodiment of the present invention, the multifunctional flexible composite material with a microstructure described above may further include the following technical features:
[0013] In some embodiments of the present invention, the micro-protrusion structure is selected from at least one of a rectangular protrusion structure, a triangular protrusion structure and a sinusoidal protrusion structure.
[0014] In some embodiments of the present invention, the molecular weight of the ultra-high molecular weight polyethylene matrix is from millions of Daltons to tens of millions of Daltons.
[0015] In some embodiments of the present invention, the aramid fiber cloth is arranged in a gradient manner, the interval between adjacent layers of the aramid fiber cloth gradually increases, and the thickness of each layer of the aramid fiber cloth is the same.
[0016] In some embodiments of the present invention, the thickness of the composite material is 0.5 mm to 10 mm.
[0017] The second aspect of the present invention provides a method for preparing the composite material described in the first aspect, comprising:
[0018] a) pressing the surface of the aramid fiber cloth through a microstructure mold to obtain an aramid fiber cloth with a microstructure on the surface;
[0019] b) arranging the aramid fiber having a micro-convex structure on the surface in a mold, adding molten ultra-high molecular weight polyethylene to the surface of the aramid fiber cloth, and then fusing the ultra-high molecular weight polyethylene and the aramid fiber cloth at a predetermined pressure and a predetermined temperature to obtain a fused material;
[0020] c) continuing to apply a predetermined pressure so that the fused material is cooled and solidified to obtain the composite material.
[0021] According to an embodiment of the present invention, the above-mentioned preparation method may further include the following technical features:
[0022] In some embodiments of the present invention, the predetermined pressure is 1 MPa to 5 MPa.
[0023] In some embodiments of the present invention, the predetermined temperature is 150-160 degrees Celsius.
[0024] The third aspect of the present invention provides the use of the multifunctional flexible composite material with a microstructure described in any embodiment of the first aspect or the multifunctional flexible composite material with a microstructure obtained according to the preparation method described in the second aspect in aerospace, automobiles, sports equipment and protective equipment.
[0025] The beneficial effects achieved by the present invention are at least:
[0026] The present invention improves the interface bonding force between aramid fiber and ultra-high molecular weight polyethylene (UHMWPE) matrix through the micro-protrusion structure on the surface of aramid fiber cloth, enhances the mechanical locking effect of the interface, and reduces interface peeling and slippage. Moreover, the rectangular, triangular and sinusoidal micro-protrusion structures not only increase the interface friction, but also effectively prevent crack propagation when subjected to force, thereby improving the overall impact toughness of the material.
[0027] The composite material aramid fiber provided by the present invention has a gradient distribution arrangement mode, and can be designed according to the specific load requirements according to the aramid fiber layers of different thicknesses to achieve functional gradient, so that the material can show excellent performance under various complex stress conditions. The gradient distribution aramid fiber layer design can more evenly disperse the stress waves generated by external impact, avoid local stress concentration, and thus improve the impact resistance of the material.
[0028] The composite material provided by the present invention is based on the low density and high strength characteristics of ultra-high molecular weight polyethylene itself, combined with the high strength characteristics of aramid fiber, so that the composite material can achieve a lower density while maintaining light weight, and is suitable for applications in the fields of aerospace, military and high-performance sports equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic structural diagram of a multifunctional flexible composite material formed by an aramid fiber cloth with a rectangular micro-convex structure on the surface and an ultra-high molecular weight polyethylene matrix provided by an embodiment of the present invention.
[0030] Figure 2 It is a schematic structural diagram of a multifunctional flexible composite material formed by an aramid fiber cloth with a triangular micro-convex structure on the surface and an ultra-high molecular weight polyethylene matrix provided by an embodiment of the present invention.
[0031] Figure 3 It is a schematic structural diagram of a multifunctional flexible composite material formed by an aramid fiber cloth with a sinusoidal micro-convex structure on the surface and an ultra-high molecular weight polyethylene matrix provided by an embodiment of the present invention.
[0032] Figure 1 to Figure 3 The reference numeral 101 is an ultra-molecular weight polyethylene matrix, 102 is an aramid fiber cloth, 1021 is a rectangular micro-protrusion structure, 1022 is a triangular micro-protrusion structure, and 1023 is a sinusoidal micro-protrusion structure. DETAILED DESCRIPTION
[0033] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0034] The present invention provides a multifunctional flexible composite material with a microstructure, the composite material comprising ultra-high molecular weight polyethylene (UHMWPE) and aramid fiber cloth; the ultra-high molecular weight polyethylene matrix is located on the surface of the aramid fiber cloth, the ultra-high molecular weight polyethylene matrix and the aramid fiber cloth are alternately arranged; wherein the surface of the aramid fiber cloth has a micro-convex structure. The composite material uses ultra-high molecular weight polyethylene (UHMWPE) as a matrix and aramid fiber cloth as a reinforcing phase, and significantly improves the interface performance and impact toughness of the material through the micro-convex structure design (such as rectangular, triangular, sinusoidal) and gradient distribution arrangement.
[0035] According to a specific embodiment, the micro-protrusion structure is one or more of a rectangular protrusion structure, a triangular protrusion structure and a sinusoidal protrusion structure. By setting these protrusions, compared with other protrusion structures, the interface can be significantly improved, and the stress distribution and energy absorption capacity can be optimized. These micro-protrusion structures can be obtained by a pre-set microstructure formation process; through this treatment, the bonding performance and overall strength with the ultra-high molecular weight polyethylene matrix can be improved.
[0036] According to the specific implementation mode, Figure 1 As shown, the aramid fiber has a rectangular micro-protrusion structure, and the aramid fiber layer has a gradient distribution arrangement.
[0037] According to the specific implementation mode, Figure 2 As shown, the aramid fiber has a triangular micro-protrusion structure, and the aramid fiber layer has a gradient distribution arrangement.
[0038] According to the specific implementation mode, Figure 3 As shown, the aramid fiber has a sinusoidal micro-protrusion structure, and the aramid fiber layer has a gradient distribution arrangement.
[0039] Herein, the ultra-high molecular weight polyethylene mentioned is a polyethylene material with a linear structure having an extremely high molecular weight. The molecular weight of ultra-high molecular weight polyethylene can be in the range of millions to tens of millions, thereby improving the impact resistance and tolerance of the composite material. According to a specific embodiment, ultra-high molecular weight polyethylene refers to a linear structure polyethylene with an average molecular weight of more than 1.5 million. According to a preferred embodiment, ultra-high molecular weight polyethylene refers to a linear structure polyethylene with an average molecular weight of more than 3 million. According to a more preferred embodiment, ultra-high molecular weight polyethylene refers to a linear structure polyethylene with an average molecular weight of more than 6 million and less than 30 million. Ultra-high molecular weight polyethylene has many excellent properties, including extremely high wear resistance, impact resistance, chemical corrosion resistance, self-lubrication and good biocompatibility, and can be used as a material for preparing polymer composite materials, but because of the extremely high molecular weight of ultra-high molecular weight polyethylene, it has certain challenges in processing and molding. The present invention creatively thinks of alternating it with aramid fiber cloth, setting micro-convex decoupling dogs on the surface of aramid fiber cloth, and preparing composite materials, which can give play to the advantages of both, and the prepared flexible material has good cushioning properties and mechanical properties.
[0040] In this article, the gradient distribution mentioned here refers to the continuous change of the composition or structure of the material in a certain direction. For example, when it is mentioned that the aramid fiber cloth is distributed and arranged in a gradient, it means that the aramid fiber cloth presents a continuous change along a certain direction.
[0041] According to a specific embodiment, the aramid fiber cloth is arranged in a gradient direction, each layer of aramid fiber has the same thickness and the spacing gradually increases, thereby optimizing its load-bearing performance and energy absorption characteristics. The impact resistance of the prepared composite material can be improved by the gradient arrangement.
[0042] According to a specific embodiment, the thickness of the composite material provided is adjustable, ranging from 0.5 mm to 10 mm, to meet the needs of different application environments. According to a specific embodiment, the thickness of each layer of aramid fiber cloth is 0.23 mm to 0.28 mm, and according to a specific embodiment, the thickness of each layer of ultra-high molecular weight polyethylene matrix is 0.1 to 0.3 mm. According to a specific embodiment, the thickness of the ultra-high molecular weight polyethylene matrix increases by 0.05 mm.
[0043] The present invention also provides a method for preparing a multifunctional composite material with a microstructure, comprising the following steps:
[0044] a) pressing the surface of the aramid fiber cloth through a microstructure mold to obtain an aramid fiber cloth having a micro-convex structure on the surface;
[0045] b) arranging the aramid fiber with a micro-convex structure on the surface in a mold, adding ultra-high molecular weight polyethylene to the surface of the aramid fiber cloth, and heating to a predetermined temperature under a predetermined pressure to fuse the ultra-high molecular weight polyethylene powder with the aramid fiber cloth;
[0046] c) maintaining the application of a predetermined pressure to allow the fused material to cool and solidify, thereby obtaining the composite material.
[0047] First, the surface of the aramid fiber is pressed to form rectangular, triangular and sinusoidal microstructures to enhance its bonding with the UHMWPE matrix; secondly, the treated aramid fiber is placed in a mold according to a designed gradient distribution, and then the ultra-high molecular weight polyethylene matrix is added for fusion. The prepared composite material has been tested for its material properties through multiple tests such as interface bonding strength, impact toughness and stress wave dispersion. The composite material effectively prevents crack propagation by improving interface friction and mechanical locking effect, and exhibits excellent impact resistance under complex stress conditions.
[0048] The ultra-high molecular weight polyethylene matrix used can be powder, particles, etc., and its molecular weight ranges from several million to tens of millions of Daltons. Ultra-high molecular weight polyethylene is used as the matrix material, and aramid fiber cloth is used as the reinforcement phase. The surface of the aramid fiber cloth is pressed by a microstructure mold to form a preset micro-convex structure on its surface. The ultra-high molecular weight polyethylene powder can be preheated to its melting temperature; or the ultra-high molecular weight polyethylene powder or particles can be directly sprinkled evenly on the surface of the aramid fiber cloth.
[0049] According to a specific embodiment, the predetermined pressure is 1 MPa to 5 MPa. According to a preferred embodiment, the predetermined pressure is 1 MPa to 3 MPa.
[0050] According to a specific embodiment, the predetermined temperature is 150-160 degrees Celsius (eg, 150-155 degrees Celsius). The predetermined pressure and the predetermined temperature are maintained for a period of time to ensure that the material is completely fused, and then cooled and solidified.
[0051] According to the specific implementation, the prepared composite material can be further subjected to heat treatment or chemical treatment to further improve its oxidation resistance and corrosion resistance and extend its service life. After heat treatment, the molecular weight of the polyethylene material will change. The heat treatment mentioned includes but is not limited to incubator insulation, radiation irradiation, and plasma treatment; the chemical treatment mentioned includes but is not limited to adding new chemical reagents for modification to improve surface properties, such as coating and coating. Through these post-treatment processes, different application scenarios can be met.
[0052] The composite materials mentioned above have been verified to have excellent performance through tests such as interface bonding strength, impact toughness, specific energy absorption, and stress wave dispersion, which are respectively improved by 16.5-28.5%, 20-25%, 8-10%, and 17-20% compared with composite materials without micro-protrusion structures. These characterizations can be carried out with reference to existing standards in the field.
[0053] For example, interface bonding strength test: shear test, tensile test and other methods are used to evaluate the interface bonding strength between aramid fiber and UHMWPE matrix in composite materials.
[0054] Another example is the impact toughness test: the Charpy impact test is used to measure the impact resistance of composite materials.
[0055] Specific energy absorption (SEA) is a measure of the impact resistance of materials, which is usually closely related to factors such as the composition, structural design, and mechanical properties of the material. Compared with traditional polymer composites, the composite material increases the contact area between the substrate and the reinforcement phase through a fine structure (rectangular, triangular and sinusoidal), thereby effectively dispersing the impact force, that is, improving the energy absorption effect.
[0056]
[0057] Wherein, P is the load borne by the material, l is the loading stroke, and M is the mass of the material.
[0058] Fracture toughness characterizes the ability of a material to prevent crack propagation. It is an inherent property of the material and is only related to the material itself, heat treatment and processing technology.
[0059] Stress wave dispersion test: Dynamic mechanical analysis (DMA) and acoustic emission testing are used to evaluate the stress wave dispersion effect of composite materials when they are impacted.
[0060] The material provides more contact points through rectangular structures, triangular structures and sinusoidal structures, which is helpful for stress transmission, reduces the generation of cracks, and improves the overall toughness of the material.
[0061]
[0062] n is the strain hardening index of the material at high temperature; E is the elastic modulus of the material at high temperature, MPa;
[0063] σ s is the yield stress of the material at high temperature, MPa;
[0064] ε f is the true strain at break during uniaxial tension at high temperature, ε f =ln(1+ψ);
[0065] ψ— Sectional shrinkage during uniaxial stretching at high temperature.
[0066] The technical solution of the present invention is described below by specific embodiments. It should be noted that these embodiments are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention.
[0067] Example 1
[0068] Example 1 provides a multifunctional flexible composite material with a fine structure, which is prepared by the following method:
[0069] First, a mold with a rectangular protrusion is processed by a CNC lathe or a wire cutting machine; then, a release agent is sprayed on the mold, and then an aramid fiber cloth is laid on the mold according to the required fiber laying direction; the fiber layer is heated / pressurized to solidify it so that it has a certain rigidity, and multiple fiber layers are prepared by the same method; then, the mixed UHMWPE slurry is injected into the mold with an aramid fiber layer bottom plate, and the other fiber layers are fixed in the container by a synchronous moving clamp according to the required thickness gradient, and gradually heated / pressurized (maintaining the injection pressure at 1 MPa and the temperature at 150°C) for solidification; after a certain period of time, the mold is unloaded, cooled, and left to stand for 24 hours to release the residual stress; and then the sample is demolded to obtain the sample.
[0070] Example 2
[0071] Example 2 provides a multifunctional flexible composite material with a fine structure, which is prepared according to the method of Example 1:
[0072] The difference between Example 2 and Example 1 is that Example 2 has a triangular micro-protrusion structure.
[0073] Example 3
[0074] Example 3 provides a multifunctional flexible composite material with a fine structure, which is prepared according to the method of Example 1:
[0075] The difference between Example 3 and Example 1 is that Example 3 has a sinusoidal micro-protrusion structure.
[0076] Comparative Example 1
[0077] Comparative Example 1 provides a multifunctional flexible composite material with a fine structure, which is prepared by referring to the method of Example 1. The difference from Example 1 is that no micro-protrusion structure is provided on the surface of the aramid fiber cloth.
[0078] Then, the composite materials of the above examples were characterized respectively, and it was found that:
[0079] Through these structural designs, the surface area of aramid fiber is increased, and the interface bonding between it and polyethylene matrix is improved, thereby improving the interface performance. Compared with composite materials without micro-protrusion structures, whether in terms of interface bonding force, impact toughness, specific energy absorption, stress wave dispersion test, etc., they have increased by about 16.5-28.5%, 20-25%, 8-10%, and 17-20%, respectively, showing better results, especially the results of sinusoidal micro-protrusions are better.
[0080] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementation methods", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.
[0081] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A multifunctional flexible composite material with a microstructure, characterized in that: It includes an ultra-high molecular weight polyethylene matrix and an adjacent aramid fiber cloth. The ultra-high molecular weight polyethylene matrix is located on the surface of the aramid fiber cloth, and the ultra-high molecular weight polyethylene matrix and the aramid fiber cloth are arranged alternately; The surface of the aramid fiber cloth has a micro-convex structure.
2. The composite material according to claim 1, characterized in that The micro-protrusion structure is selected from at least one of a rectangular protrusion structure, a triangular protrusion structure and a sinusoidal protrusion structure.
3. The composite material according to claim 1, characterized in that The molecular weight of the ultra-high molecular weight polyethylene matrix is greater than 6 million and less than 30 million.
4. The composite material according to claim 1, characterized in that The aramid fiber cloth is arranged in a gradient manner, the interval between adjacent layers of the aramid fiber cloth gradually increases, and the thickness of each layer of the aramid fiber cloth is the same.
5. The composite material according to claim 1, characterized in that The thickness of the composite material is 0.5 mm to 10 mm.
6. The composite material according to claim 1, characterized in that The thickness of the aramid fiber cloth is 0.23 mm to 0.28 mm, and the thickness of the ultra-high molecular weight polyethylene matrix is 0.1 mm to 0.3 mm.
7. The method for preparing a composite material according to any one of claims 1 to 6, characterized in that: include: a) pressing the surface of the aramid fiber cloth through a microstructure mold to obtain an aramid fiber cloth having a micro-convex structure on the surface; b) arranging the aramid fiber with a micro-convex structure on the surface in a mold, adding molten ultra-high molecular weight polyethylene to the surface of the aramid fiber cloth, and heating to a predetermined temperature under a predetermined pressure to fuse the ultra-high molecular weight polyethylene and the aramid fiber cloth to obtain a fused material; c) continuing to apply a predetermined pressure so that the fused material is cooled and solidified to obtain the composite material.
8. The preparation method according to claim 1, characterized in that: The predetermined pressure is 1 MPa to 5 MPa.
9. The preparation method according to claim 1, characterized in that: The predetermined temperature is 150-160 degrees Celsius.
10. Use of the multifunctional flexible composite material with a microstructure according to any one of claims 1 to 6 or the multifunctional flexible composite material with a microstructure obtained by the preparation method according to any one of claims 7 to 9 in aerospace, automobiles, sports equipment and protective equipment.
Citation Information
Patent Citations
Light weight trauma reducing body armor
CN105939850A
Wave type carbon felt electromagnetic shielding structural body and preparation method thereof
CN109263172A
Multilayer composite material and manufacturing method thereof
CN113942156A
Fiber metal laminate for enhancing composite interface connection and preparation method thereof
CN114103303A
Copper-clad plate of ionic-migration-resisting structure
CN204263647U